Effect of High Pressure and Sub-Zero Temperature on Total Antioxidant Capacity and the Content of Vitamin C, Fatty Acids and Secondary Products of Lipid Oxidation in Human Milk - Martysiak-Żurowska Dorota; Puta Małgorzata; Barczak Natalia; Dąbrowska Joanna; Malinowska-Pańczyk Edyta; Kiełbratowska Bogumiła; Kołodziejska Ilona (Polish Journal of Food and Nutrition Sciences)
The objective of this study was to compare of the effects of high pressure of 193 MPa at −20°C and Low Temperature Long Time pasteurization (LTLT or holder pasteurization, 62.5°C, 30 min) on the content and composition of fatty acids (FAs), concentrations of secondary products of lipid oxidation (TBARS), the total antioxidant capacity (TAC), total vitamin C and ascorbic acid (AsA) content in human milk. It was shown that no significant changes in the content and composition of FAs and TBARS levels were noted in both pressurized and LTLT pasteurized milk samples. The results obtained indicate that the antioxidant properties in pressurized human milk were also not affected. In the case of the pasteurized samples only slight (approx. 6%) and statistically insignificant decrease was observed in the Trolox equivalent antioxidant capacity (TEAC) values. Pasteurization significantly reduced the content of total vitamin C and AsA, by 35% and 24%, respectively. A minor and statistically insignificant (approx. 6%) decrease in vitamin C levels was observed in milk treated with high pressure. However, a significant decrease (by more than 11%) occurred in these conditions in AsA concentrations. The influence of high pressure treatment on AsA levels and the lack of significant changes in TEAC values point to the relative stability of the remaining antioxidant components in human milk. Further research is needed to determine the effects of high pressure of approximately 200 MPa and sub-zero temperatures on, mainly thermolabile, components of human milk, which are degraded by LTLT pasteurization.